2016
DOI: 10.1513/annalsats.201509-576oc
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Pediatric Bronchoscopy Outcomes Using an Electronic Medical Record

Abstract: An EMR system may be used to track procedural outcomes. Unplanned outcomes after flexible bronchoscopy were infrequent at our institution. Children who underwent multiple procedures had unplanned outcomes more often; however, the subset of children who underwent coordinated procedures through our multidisciplinary aerodigestive clinic did not demonstrate this increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 27 publications
7
33
0
1
Order By: Relevance
“…In accordance with previous studies, we have demonstrated that children below 2 years of age are at a higher risk for severe complications . Similar findings related to other invasive procedures have also been reported in children in this age group .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In accordance with previous studies, we have demonstrated that children below 2 years of age are at a higher risk for severe complications . Similar findings related to other invasive procedures have also been reported in children in this age group .…”
Section: Discussionsupporting
confidence: 92%
“…Hence, comparison of overall numbers is difficult, since postprocedural complications accounted for most adverse events in our study. DeBoer et al developed and tested a method for analyzing flexible bronchoscopy outcomes by using an electronic medical recording system. A total of 1062 procedures were analyzed and complications were defined as events interrupting or terminating the bronchoscopy, differing considerably form the adverse events included in our analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations